PERFORMANCE MEASUREMENT, REWARD SYSTEM AND EMPLOYEES’ DYSFUNCTIONAL BEHAVOURS: EVIDENCES FROM MANUFACTURING SMALL AND MEDIUM ENTERPRISES IN KWARA STATE, NIGERIA - Sann, Mubaraq; Mustapha, Abdulrasaq; Lawal, Wahab (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
Expectedly, control systems are design to align individual objectives with organization-wide objectives. However, this seems not to be observable in most cases going by the series of organization problems attributed to employee dysfunctional behaviours. This study attempts to investigate the extent to which performance measurement and reward control systems influence employees’ dysfunctional behavior in manufacturing companies in Kwara State. To achieve this objective, well-structured questionnaires were sent to randomly select one hundred and thirty-eight (138) line managers as respondents. Ordinary least square regression analysis was employed in testing the hypotheses raised. The study found that reward system and performance measurement system have significant negative effect on the employee’s dysfunctional behavior practice at 5% significant level (P-value of 0.034 and 0.048 respectively). This implies that reward system and performance measurement have capacity to restraint level of employee dysfunctional behaviour. The study therefore recommends that the management of companies should use both intrinsic and extrinsic reward system as well as the use of balance score card for performance measurement in influencing employees to pursue organization objectives.